Pola Teknik Budi Daya dan Sifat Kimia Tanah yang Berhubungan dengan Penyakit Blas pada Padi Sawah - Andriyani , Yuyun; Suryo Wiyono (Jurnal Fitopatologi Indonesia, 2021)
Pattern of Cultivation Technique and Soil Chemical Properties Associated with Blast Disease of Paddy Rice Blast caused by Pyricularia oryzae is a most destructive diseases of rice in all rice producing countries. However severe blast infestation on paddy rice in Indonesia is relatively new, it is previously known as main disease of upland rice. This study aimed to determine the agronomic and soil factors associated with development of blast disease of paddy rice. Blast disease was assessed on 50 plots of paddy field by using IRRI score system. Farmers growing paddy rice in observed plots were interviewed using structured questionnaire on cultivation techniques includes varieties, NPK organic and synthetic fertilizers rate, insecticides, fungicides and herbicides uses. Soil chemical analysis was done on pH, C organic, N, P, K, Ca, Mg, Si, Zn, Mn, Cu of soils obtained from severe and low severity of blast disease, with five samples for each category. Data of agronomical factors (varieties, fertilizers rate, pesticides uses, organic matter uses) was cross tabulated against two level of blast severity and furthermore analyzed using χ2 test for significance association. Soil chemical properties that has different disease severity were analyzed. The agronomic factors associated with the high severity of lowland rice blast disease involves the use of Ciherang varieties, high frequency pesticides, and herbicides. Soil properties related to the rate of disease outbreak involves levels of N, P, K, S, Si, and soil micro-elements.